Families and States. A necessary relationship in the achievement of the Sustainable Development Goals (Islas, 2021)
This article ponders families based on their active role as an institution and social group and on their value as a social entity in the reproduction of its members and their financial, cultural and spiritual satisfaction. Reference is made to the Objectives and Goals contained in the 2030 Agenda which are headed towards the important and necessary work of the States in relation to families, through the design of the family policies that benefit their comprehensive development, and in the achievement of the Sustainable Development Goals. Challenges are expressed in relation to the achievement of the Objectives and Goals, as well as to the boost and promulgation of a greater participation of families together with the State in matters that concern them.
Keywords: Families; sustainable development; sustainable development goals